Longitudinal dynamics of plasma bile acids and their associations with physiological parameters and fecal microbiome during the transition period in dairy cows - Feixiang Fan; Liang Chen; Huizeng Sun; Jianxin Liu; Kailun Yang; Fengfei Gu (Animal Bioscience)
Objective The aim of this study is to investigate the dynamic changes of plasma bile acids (BA) and their correlations with physiological parameters and fecal microbiome in transitional dairy cows. Methods Twenty multiparous dairy cows were selected, the blood and fecal samples were collected on d −21, −7, +7, and +21 of calving. The targeted metabolome and 16s rDNA ampicon sequencing were utilized to identify BA profiles and fecal microbial composition, respectively. Results A total of 32 BAs were found, comprising 9 primary BAs (PBA) and 23 secondary BAs (SBA). Majority of the PBAs (7 out to 9) and SBAs (15 out to 23) exhibited significant increases postpartum compared to prepartum levels. Notably, ursodeoxycholic acid, taurocholic acid and 7-ketodeoxycholic acid showed higher importance. Correlation analysis showed the BAs concentrations positively correlated with the concentrations of aspartate aminotransferase, total antioxidant capacity, and glutathione peroxidase, while exhibiting substantial negative correlation with triglyceride concentrations. A decline in bacterial alpha diversity in postpartum and significantly different β-diversity were observed. Furthermore, 30 distingtive genera were identified over the transition period. Among these, six and eleven biomarkers such as Alistipes and Ruminococcaceae_UCG_014 were identified at +7 d and +21 d, respectively. Furthermore, the abundances of choloylglycine hydrolase and 7-alpha-hydroxysteroid dehydrogenase which are involved in SBA biosynthesis were significantly higher postpartum as determined by PICRUSt2 analysis over the transition period. Conclusion The BA profile and concentrations underwent significant changes during the transition period in dairy cows and these changes are closely related to the periparturient health of the cows. Ursodeoxycholic acid and Alistipes was identified as the pivotal BA and microbial genus. Our study elucidates these metabolic processes, providing useful insights into strategies for enhancing the nutrition and well-being of perinatal dairy cows.